ANTROZOOLOGÍA: DEFINICIONES, ÁREAS DE DESARROLLO Y APLICACIONES PRÁCTICAS PARA PROFESIONALES DE LA SALUD - Marcos Diaz Videla; María Alejandra Olarte; Javier Martin Camacho (European Scientific Journal, ESJ, 2015)
Human nature has been molded by its interactions with animals, and these have played an essential role in the development of human societies by providing material, instrumental, and emotional resources. Despite the undeniable importance of animals in different aspects of human life, the scientific community has neglected the study of the interaction between human and other species until recently. This was the focus of interest of the anthrozoology: young interdisciplinary science devoted in the study of the interactions between human beings and animals. Anthrozoology has received a growing interest since its origin, little longer than thirty years ago, with a steady increase in its developments and publications. We performed a review of the scientific literature and present the development of a thematic group which comprehends five areas: (1) Involved evolutionary factors, (2) Developmental and learning processes, (3) Associated cultural, collective, and individual factors, (4) Health and well-being, and (5) Animals in the human family. Also, we discuss the anthrozoology developments according to its relevance and usage in health professionals’ clinical practice.